Is graphene on copper doped?. Issue 9 (22nd July 2013) - Marsden, Alexander J.; Asensio, Maria‐Carmen; Avila, José; Dudin, Pavel; Barinov, Alexei; Moras, Paolo; Sheverdyaeva, Polina M.; White, Thomas W.; Maskery, Ian; Costantini, Giovanni; Wilson, Neil R.; Bell, Gavin R.
Abstract Angle‐resolved photoemission spectroscopy (ARPES) and X‐ray photoemission spectroscopy have been used to characterise epitaxially ordered graphene grown on copper foil by low‐pressure chemical vapour deposition. A short vacuum anneal to 200 °C allows observation of ordered low energy electron diffraction patterns. High quality Dirac cones are measured in ARPES with the Dirac point at the Fermi level (undoped graphene). Annealing above 300 °C produces n‐type doping in the graphene with up to 350 meV shift in Fermi level, and opens a band gap of around 100 meV. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Dirac cone dispersion for graphene on Cu foil after vacuum anneals (left: 200 °C, undoped; right: 500 °C, n‐doped). Centre: low energy electron diffraction from graphene on Cu foil after 200 °C anneal. Data from Antares (SOLEIL). (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)